Economic support personal networks of rural entrepreneurships - Cid-Aguayo, Beatriz E.; Sandoval-Nazal, Daniel; Carrasco, Juan Antonio (2013)
The Polanyian discussion about the embeddedness of the economy in social relations, finds a new stream through the social network analysis, from which is possible to map the cooperation relations that underlie economic ones. From the latter, this article shows the analysis of nine family-based economic entrepreneurships linked to a cooperative of services and agrofood products. Through personal networks analysis we mapped and highlighted the diversity of collaborations, monetary and non-monetary exchanges the entrepreneurships perform with their networks. In consequence, we characterized the support networks identifying the different economic exercises that take part in relation to the entrepreneurships. By this way, we accounted some relevant aspects such as the formality or informality condition, the entrepreneurships level, the networks' cohesion and the types of exchange, among other issues.
Keywords: embeddedness; rural entrepreneurships; social networks